2021
DOI: 10.1029/2021jd034568
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Impacts of Tropopause‐Overshooting Convection on the Chemical Composition of the Upper Troposphere and Lower Stratosphere

Abstract: Moist convection frequently reaches the tropopause in the United States and mixes air between the troposphere and stratosphere • Tropopause-overshooting convection occurring during May drastically increases lower stratospheric water vapor mixing ratios • The impact that convection has on upper troposphere and lower stratosphere (UTLS) composition appears to largely depend on the height of the tropopause

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…It is clearly visible that CIWC transects the tropopause in the region of strong convective activity, which means that ice is transported above the tropopause. This emerges, in particular, at lower tropopause altitudes at the center of the upper-level trough, confirming findings of Phoenix and Homeyer (2021). No such signal is observed over the Atlantic Ocean in cirrus regions that are driven by large-scale ascent and that exhibit a familiar homogeneous shape of the tropopause above.…”
Section: D Exploration Of Convection and The Tropopausesupporting
confidence: 86%
See 1 more Smart Citation
“…It is clearly visible that CIWC transects the tropopause in the region of strong convective activity, which means that ice is transported above the tropopause. This emerges, in particular, at lower tropopause altitudes at the center of the upper-level trough, confirming findings of Phoenix and Homeyer (2021). No such signal is observed over the Atlantic Ocean in cirrus regions that are driven by large-scale ascent and that exhibit a familiar homogeneous shape of the tropopause above.…”
Section: D Exploration Of Convection and The Tropopausesupporting
confidence: 86%
“…The ascent proceeds until the convective air reaches the tropopause and pushes into the stably stratified lower stratosphere from where most of the air will return back down. However, modeling and observational studies have shown that midlatitude overshooting convection moistens the lower stratosphere through injection of water vapor and ice (e.g., Dessler and Sherwood 2004;Hegglin et al 2004;Ray 2004;Mullendore et al 2005;Homeyer et al 2014;Homeyer 2015;Smith et al 2017;Phoenix and Homeyer 2021). The role of convection for the humidity distribution in the stratosphere and its representation in numerical models is an active field of research with many AFFILIATIONS: Schäfler-Institut für Physik der Atmosphäre, Deutsches Zentrum für Luft-und Raumfahrt, Oberpfaffenhofen, Germany; Rautenhaus-Visual Data Analysis Group, Regional Computing Centre, Universität Hamburg, Hamburg, Germany open questions regarding the transport mechanisms, the amount of moisture that is injected, and the impact of this process in a changing climate (Smith 2021).…”
Section: Overshooting Convectionmentioning
confidence: 99%
“…In the midlatitude lower stratosphere, particularly over North America, where the tropopause level is lower and the saturation mixing ratio is higher compared to the tropics, the impact of convective overshooting could be larger. Phoenix and Homeyer (2021) have shown that convective storms can increase the mean lower stratospheric water vapor by 20%–30% by evaluating multiple convective storms over the U.S in model simulations. Numerous observational studies also investigated this question.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies identify a minimal role of convective contributions to stratospheric water vapor (∼10%), these are typically restricted in focus to tropical convection and impacts on the stratospheric overworld (e.g., Dauhut and Hohenegger, 2022;Ueyama et al, 2023, and references therein). Studies that focus on convection within extratropical environments, subtropical environments, and monsoon regions often show substantial contributions from convection to the LMS H 2 O concentration locally (Hanisco et al, 2007;Dessler and Sherwood, 2004;Smith et al, 2017;Jensen et al, 2020;Tinney and Homeyer, 2021;Gordon and Homeyer, 2022;Phoenix and Homeyer, 2021;Homeyer et al, 2014;Hegglin et al, 2004;Mullendore et al, 2005;Schwartz et al, 2013;Werner et al, 2020;O'Neill et al, 2021). Overall, the contributions of any specific process to the stratospheric H 2 O budget, especially deep convection, remains a topic of scientific debate.…”
Section: Introductionmentioning
confidence: 99%